2018
DOI: 10.2147/ott.s156792
|View full text |Cite
|
Sign up to set email alerts
|

Effects of propofol-based total intravenous anesthesia on gastric cancer: a retrospective study

Abstract: BackgroundSeveral kinds of cancer surgeries with propofol-based total intravenous anesthesia (TIVA) have been shown to have better outcomes than those with sevoflurane-based inhalational anesthesia (INHA). However, the effects of this anesthetic technique have not been investigated in patients with gastric cancer. In this study, the authors retrospectively examined the link between the choice of anesthetic technique and overall survival in patients undergoing gastric cancer resection.MethodsWe conducted a retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(105 citation statements)
references
References 44 publications
5
92
1
2
Order By: Relevance
“…All studies except Yan et al 19 adjusted for at least one of the following variables in their multivariate analyses: age, body mass index, comorbidities, preoperative therapy, pathologic stage or grade of cancer, and intraoperative anesthetic interventions such as epidural or blood transfusion. [12][13][14][15][16][17][18]20,21…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…All studies except Yan et al 19 adjusted for at least one of the following variables in their multivariate analyses: age, body mass index, comorbidities, preoperative therapy, pathologic stage or grade of cancer, and intraoperative anesthetic interventions such as epidural or blood transfusion. [12][13][14][15][16][17][18]20,21…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…All the nine retrospective studies had a NOS C 7 demonstrating good methodologic quality and a low risk of bias. [12][13][14][15][16][17][18]20,21 The single prospective RCT included in this meta-analysis had a low risk of bias for each domain. 19…”
Section: Additional Analyses and Risk Of Bias Across Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…found that the effect of propofol on cellular immune responses was slightly lower than that of sevoflurane . In 2018, a retrospective analysis indicated that propofol‐based total intravenous anesthesia could be associated with improved survival in patients undergoing gastric cancer resection . Liu et al.…”
Section: Immune Function Changesmentioning
confidence: 99%
“…71 In 2018, a retrospective analysis indicated that propofol-based total intravenous anesthesia could be associated with improved survival in patients undergoing gastric cancer resection. 72 Liu et al proved that propofol was superior to isoflurane and enflurane at inhibiting serum IL-8 secretion and increasing IL-10 secretion and could be considered a better anesthetic agent for inhibiting a traumatic inflammatory response. 73 However, a recent study showed that propofol was not better than sevoflurane in terms of NK and CTL cell counts and apoptotic rates during anesthesia for breast cancer surgery in a clinical setting.…”
Section: Immune Function Changesmentioning
confidence: 99%